Supporting the decision on dashboard design charts - Costa, C.; Aparicio, M. (Proceedings of 254th The IIER International Conference, 2019)
Different decisions types need differentiation of information presentation; management requires adequate tools for the decision-making process. Business value insights are improved with better information visualization, therefore improving decision making. In this study, it presented a theoretical review based on three main areas: management, reporting, and visualization. Upon this theory review, we identify the primary dimension. Those dimensions are used to embody decisions that maybe incorporate in a decision tree. This decision tree may be helpful in the choice of adequate data visualization form managerial dashboards. For future works, we suggest conducting an empirical work that uses this decision tree to understand the impacts on its usage on management context better.